Novel and sustainable methods to develop greener polymers - Correia d'Almeida Mendes Gameiro, Mariana Isabel (2019)
This Thesis reports the development of green approaches towards the synthesis of novel polyesters. Generally, polyesters are synthesised using harsh conditions (such as high temperatures) and rely upon petrochemical-derived building blocks. By using biomass, more specifically plant oil derived sources, such as glycerol and vernolic acid (fatty acid, FA), we will explore a more renewable approach. In addition, scCO2 will be explored as a novel solvent and processing aid and also, immobilised enzymes will be used as biocatalysts.